Finite Element Analysis of the Flexural Behavior of Steel Plate–High-Performance Concrete (HPC) Slab and Beam Composite Structures - Jian-Peng Li; Lu-Yao Zhang; Ying-Jie Zhu; Guo Zhao; Fu-Zhong Liu; Tao Zhang (Buildings)
This paper studied the flexural behavior of flat steel–HPC composite beams and corrugated steel–HPC composite slabs using finite element analysis. The accuracy and reliability of the finite element model were verified by comparing it with related experimental data in the literature. The influence of different factors on the flexural bearing capacity of the composite slab/beam is discussed. Increasing the concrete thickness, friction coefficient, concrete strength, and wave height of a corrugated steel plate and employing an optimized rebar configuration significantly enhanced the flexural behavior. Remarkably, increasing the thickness of the steel plate and the number of studs also improved the flexural bearing capacity, but an over-reinforcement phenomenon could easily occur, not being conducive to optimal structural performance. An equation for calculating the flexural bearing capacity of steel–HPC composite slab/beam structures considering the effects of the number of studs and the friction coefficient is proposed. The rationality of the proposed method was verified through the finite element results, providing a more accurate method for designing steel–HPC composite structures.